2018
DOI: 10.1177/2050312118801220
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the feasibility of parent participation in a commercial weight loss program to improve child body mass index and weight-related health behaviors

Abstract: Objectives:Little is known about how children’s health might be affected by parents’ participation in commercial weight loss programs. Given that more than 3.2 million people subscribe to just one commercial weight loss program, Weight Watchers, any secondary effects on children’s weight-related health behaviors (e.g. dietary behaviors, physical activity, and sedentary time) and body mass index from parent participation in commercial weight loss programs may have significant public health implications. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…Potential participants were excluded if they had: a major medical condition that would prevent participation in MVPA or would be a contraindication for energy expenditure, were using a prescribed weight-loss drug, were enrolled in an additional weight-loss program, or were likely to move out of Oregon within the following 12 months. The recruitment method for the caregiver-child dyads has been described elsewhere (Song & Bonds, 2020; Song et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential participants were excluded if they had: a major medical condition that would prevent participation in MVPA or would be a contraindication for energy expenditure, were using a prescribed weight-loss drug, were enrolled in an additional weight-loss program, or were likely to move out of Oregon within the following 12 months. The recruitment method for the caregiver-child dyads has been described elsewhere (Song & Bonds, 2020; Song et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Brief recruitment presentations were given at meeting locations once every 12 weeks by our study team. Potential participants provided contact information at the meeting via a sign-up sheet, and our team then followed up with the interested participants (Song et al, 2018). Potential participants were also invited to learn more by calling a toll-free telephone number or emailing to the provided study email address.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have focused on how parental engagement in adult medical weight management (MWM) programs affects dependent children living in the home, and specifically, how family participation in exercise associates with the children’s own physical activity engagement. Notably, Song and colleagues (2018) assessed parental participation in a commercial weight loss program and its influence on child outcomes [ 19 ]. While the study reported a significant correlation between the parents’ and children’s decrease in saturated fat consumption and a decline in family meals eaten outside of the home, they did not find any significant changes in the parents’ and children’s physical activity or an association between their rates of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…The current orientation for improving adherence to treatments in pediatrics focuses on motivation, problem-solving skills, and reduction of post-treatment influence, resorting to a number of tools including web-based programs [ 6 , 7 ], “exergaming” [ 8 , 9 , 10 ], school interventions [ 11 ], summer camp [ 12 ], parent engagement [ 13 , 14 , 15 ], and automated mobile technology (MT) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Studies focused on mobile phone interventions to improve lifestyle and preventing overweight and obesity are attracting interest in both the adult and pediatric population.…”
Section: Introductionmentioning
confidence: 99%